2022
DOI: 10.3233/ajw220049
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination in Aquatic and Terrestrial Animals Resulted from Anthropogenic Activities in Indonesia: A Review

Abstract: Hazardous metal pollution has raised a global concern to its increasing trend in response to industrial growth. As an emerging economy, Indonesia starts to receive a backlash of increasing anthropogenic activities resulting in higher emission of heavy metal pollutants. Heavy metals are non-biodegradable pollutants and toxic to humans and other living organisms. Herein, we have reviewed published investigations on the contamination of heavy metals (Pb, Cu, Hg, Ni, Cd, Zn and As) in aquatic and terrestrial anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Meanwhile, a new class of antibiotics had not been developed for over three decades [1]. Research on antimicrobial substances using natural resources has become a serious discussion by researchers [2][3][4][5][6][7][8][9][10][11][12]. The utilization of plant secondary metabolites to cure various illnesses was an ancient practice of taking the resources available in markets, gardens, horticulture backyards, and areas with pristine vegetation [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a new class of antibiotics had not been developed for over three decades [1]. Research on antimicrobial substances using natural resources has become a serious discussion by researchers [2][3][4][5][6][7][8][9][10][11][12]. The utilization of plant secondary metabolites to cure various illnesses was an ancient practice of taking the resources available in markets, gardens, horticulture backyards, and areas with pristine vegetation [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that pollutants are generally introduced into the environment as a result of anthropogenic activities. Among them, heavy metals, such as Cd, Cu, Hg, Ni, Zn, and Pb, are known to be toxic to living organisms and to present high potential risks to human health due to their accumulation in the food chain due to anthropogenic activities [1,2]. Alongside these pollutants, arsenic (As) contamination in groundwater has recently become a global issue [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, heavy metals, such as Cd, Cu, Hg, Ni, Zn, and Pb, are known to be toxic to living organisms and to present high potential risks to human health due to their accumulation in the food chain due to anthropogenic activities [1,2]. Alongside these pollutants, arsenic (As) contamination in groundwater has recently become a global issue [2][3][4][5]. In Burkina Faso, it was reported that the groundwaters in several localities were polluted with arsenic, whose concentrations in pit and drilling waters are extremely high compared to the World Health Organization's (WHO) standard value (0.01 mg/L) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Both the U.S. Environmental Protection Agency and the International Agency for Cancer Research classify them as human carcinogens [6]. For instance, the levels of contamination in aquatic and terrestrial animals attributed to anthropogenic activities in Indonesia were found to have exceeded the tolerable limits of international standards, according to some reports [7][8][9]. Lead species are considered the most hazardous pollutants.…”
Section: Introductionmentioning
confidence: 99%